AIRPORT NOISE LEVEL EVENT WITH HYPERTENSION IN THE CARGO INTERNATIONAL AIRPORT WORKERS ADISUCIPTO YOGYAKARTA - Indra, I Made; Lesmana, Tedy Candra; Basuki, Prasiwi Putri (STIKES Wira Husada Yogyakarta, 2013)
ABSTRACT Background: People who work in the airport would experience interferencenoise is higher than the communities around the airport. Aircraft generatednoise will cause emotional disturbances and increased job stress triggersincreased blood pressure on airport workers.